2019
DOI: 10.1109/tvt.2018.2880817
|View full text |Cite
|
Sign up to set email alerts
|

Optical Mobile Communications: Principles, Implementation, and Performance Analysis

Abstract: Owing to the rapid growth of mobile data communication and spectrum crunch at lower radio frequency, utilizing high frequency spectrum such as millimeter wave for ultra-high data rate mobile communications becomes necessary. Yet the propagation behaviors of high frequency radio waves make mobile communications rather challenging with a lot of technical problems, such as very large propagation loss. In this paper, we propose a novel approach, referred to as optical mobile communications (OMC), to cater to the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 49 publications
0
24
0
Order By: Relevance
“…Some concrete future research directions and novel technologies, which can open new vistas for the future, have been added in our study. Our research results would be integrated with some advanced research directions including cybersecurity, (39) green communication, (40) cognitive radio, (41) and optical mobile communications technologies (42) to further improve energy efficiency and autonomy in SHCM.…”
Section: Discussionmentioning
confidence: 99%
“…Some concrete future research directions and novel technologies, which can open new vistas for the future, have been added in our study. Our research results would be integrated with some advanced research directions including cybersecurity, (39) green communication, (40) cognitive radio, (41) and optical mobile communications technologies (42) to further improve energy efficiency and autonomy in SHCM.…”
Section: Discussionmentioning
confidence: 99%
“…Initial results have shown that coherent reception is feasible and achieves higher Rx sensitivity [289]. Besides, light beams can achieve near perfect energy concentration, making them a promising solution to achieve highest multiplexing gains while enabling very high energy efficiency [290]. The super high directional gain also makes the information transmission unlikely to be eavesdropped on, making the links safer than their RF counterparts [291].…”
Section: Optical Frequency Bandsmentioning
confidence: 99%
“…In this case a gridof-beam and an associated beam-switching approach might be more advantageous. Another promising way to manage high-speed mobility and multi-user access in OWC is the newly proposed optical mobile communication (OMC) technology [290]. OMC uses optical phased arrays to steer optical beams to mobile users with high energy efficiency.…”
Section: Optical Frequency Bandsmentioning
confidence: 99%
“…I NTELLIGENT transportation systems (ITSs) are currently a promising area of research, whose key features include autonomous vehicle management, traffic efficiency, road safety, and inter-vehicle and inter-passenger communication [1]. Due to the rapid development of mobile communication systems, radiofrequency (RF) spectrum is not sufficient to support the requirements for high throughput [2]. Moreover, along with the density of vehicles, communications through tunnels and subway using RF based GPS signals are becoming a challenging issues for ITS.…”
Section: Introductionmentioning
confidence: 99%